Curcuminoid WZ35 synergize with cisplatin by inducing ROS production and inhibiting TrxR1 activity in gastric cancer cells - Wei He; Yiqun Xia; Peihai Cao; Lin Hong; Tingting Zhang; Xin Shen; Peisen Zheng; Huanpei Shen; Guang Liang; Peng Zou (Journal of Experimental & Clinical Cancer Research, 2019)
Abstract Background Cisplatin is one of the most widely used chemotherapeutic agents, but its efficacy is limited by its side effects. Hence, it is of great significance to develop novel agents to synergize with cisplatin and decrease side effects. In our previous study, we demonstrated that WZ35, a novel curcumin analogue, exhibited potent anti-cancer effects in vitro and in vivo. Here, we investigated whether WZ35 synergize to potentiate cisplatin activity in gastric cancer cells. Methods Cell apoptosis and cellular ROS levels were analyzed by flow cytometry. TrxR1 activity in gastric cells or tumor tissues was determined by the endpoint insulin reduction assay. Western blot was used to analyze the levels of indicated molecules. Nude mice xenograft model was used to test the effects of WZ35 and cisplatin combination on gastric cancer cell growth in vivo. Results We found that WZ35 significantly enhanced cisplatin-induced cell growth inhibition and apoptosis in gastric cancer cells. Further mechanism study showed that WZ35 synergized the anti-tumor effects of cisplatin by inhibiting TrxR1 activity. By inhibiting TrxR1 activity, WZ35 combined with cisplatin markedly induced the production of ROS, activated p38 and JNK signaling pathways, and eventually induced apoptosis of gastric cancer cells. In vivo, WZ35 combined with cisplatin significantly suppressed tumor growth in a gastric cancer xenograft model, and effectively reduced the activity of TrxR1 in tumor tissues. Remarkably, WZ35 attenuated the body weight loss evoked by cisplatin treatment. Conclusion This study elucidated the underlying mechanisms of synergistic effect of WZ35 and cisplatin, and suggest that such a combinational treatment might potentially become a more effective regimen in gastric cancer therapy.